2019
DOI: 10.1097/md.0000000000016663
|View full text |Cite
|
Sign up to set email alerts
|

Antecolic reconstruction is associated with a lower incidence of delayed gastric emptying compared to retrocolic technique after Whipple or pylorus-preserving pancreaticoduodenectomy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
0
10
0
1
Order By: Relevance
“…Other studies have examined approaches that might influence the risk of DGE. Some meta-analyses have suggested antecolic, Billroth II to be favourable for DGE 14–16 . Of meta-analyses that specifically investigated resection of the pylorus, Klaiber and colleagues found no difference between PR and PP in a subgroup analysis of RCTs 13 , similar to the findings of this present network meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have examined approaches that might influence the risk of DGE. Some meta-analyses have suggested antecolic, Billroth II to be favourable for DGE 14–16 . Of meta-analyses that specifically investigated resection of the pylorus, Klaiber and colleagues found no difference between PR and PP in a subgroup analysis of RCTs 13 , similar to the findings of this present network meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The recent pylorus resection or pylorus preservation (PROPP) RCT and several meta-analyses have shown comparable DGE rates between pylorus-preserving and pylorus-resecting operations, although comparisons between the different resections are limited 3 , 12 , 13 . Previous meta-analyses have also suggested that antecolic gastrojejunostomy is the more effective route for minimizing DGE 14–16 , but again evidence is conflicting 17 . Similarly, it remains controversial whether a simple Billroth II or Roux-en-Y reconstruction makes a difference 16 , 18–21 and what value is gained from Braun enteroenterostomy, to prevent bile reflux, in terms of DGE rates 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has attempted to ascertain an approach at each step of PD that is optimal for minimising DGE. A few meta-analyses have suggested antecolic, Billroth II to be favourable for DGE 1618 . Of meta-analyses that specifically investigated the resection of the pylorus; Klaiber et al found no difference between PR and PP PD in a subgroup analysis of RCTs 12 , further confirmed by this NMA.…”
Section: Discussionmentioning
confidence: 99%
“…Pylorus resecting PD has been suggested to be favourable to pylorus preservation in reducing DGE rates as retaining the pylorus is thought to retain the propulsive activity of the stomach, but comparisons between the CW, PP and PR are limited 3,12,15 . Previous meta-analyses also suggested antecolic gastro-jejunostomy to be the most effective route for minimising DGE 1618 , however, the evidence is conflicting 19 . Similarly, it remains controversial whether Billroth II or Roux-en-Y reconstruction is favourable 18,20–23 .…”
Section: Introductionmentioning
confidence: 99%
“…The recent pylorus resection or pylorus preservation (PROPP) RCT and several meta-analyses have shown comparable DGE rates between pylorus-preserving and pylorus-resecting operations, although comparisons between the different resections are limited 3,12,13 . Previous meta-analyses have also suggested that antecolic gastrojejunostomy is the more effective route for minimizing DGE [14][15][16] , but again evidence is conflicting 17 . Similarly, it remains controversial whether a simple Billroth II or Roux-en-Y reconstruction makes a difference 16,[18][19][20][21] and what value is gained from Braun enteroenterostomy, to prevent bile reflux, in terms of DGE rates 22 .…”
Section: Introductionmentioning
confidence: 99%